Toland and Adam Smith’s Posthumous Work (Diametros, 2014)
In this paper I offer a speculative answer to the question why Adam Smith, who burned nearly all of his papers, arranged for posthumous publication for a number of his essays. I rely on a number of hints in those essays and put them in the context of eighteenth century natural philosophy. I argue that those hints trace back to John Toland and Spinozism.